Evaluation of Virulence Factors of Yeasts Isolated from Cancer Patients and their Surrounding Environment - Al-Darraji, Zahraa D. G.; Ameen, Mohanad K. M. (Scientific Journal of Medical Research, 2023)
Objective: This study included the determination of virulence factors for yeasts isolated from cancer patients and their surrounding environment through the study of extracellular hydrolytic enzymes and biofilms. Methods: Using particular media for enzymes, there were three enzymes used, phospholipase, proteinase, and hemolysin, to examine the enzyme activity of yeasts isolated during the study. The microtiter plate method was also used for the purpose of biofilm detection. Results: The results showed the activity of yeasts towards enzymes as well as biofilm. The largest percentage of yeasts showed proteinase and hemolysin activity. It reached 80 (78.43%) and 79 (77.45%), respectively, while phospholipase was the lowest percentage 49(48.03%). Also, the isolates showed their effectiveness in biofilm formation, as 73 (71.56%) isolates produced biofilm while 29 (28.43%) did not. Conclusions: The present work concluded that the yeast isolates collected from cancer patients and the environment surrounding them, the great majority of them possess enzymatic activity also have the ability to form biofilms, and this matter is worrying and dangerous for theme because of their presence in the environments of immunocompromised patients and their chance of infection with these yeasts were exactly existent.